Electrochemical lithiation/delithiation of SnP2O7 observed by in situ XRD and ex situ7Li/31P NMR, and 119Sn Mössbauer spectroscopy. Issue 15 (31st March 2016) - Bezza, Ilham; Kaus, Maximilian; Riekehr, Lars; Pfaffmann, Lukas; Doyle, Stephen; Indris, Sylvio; Ehrenberg, Helmut; Solhy, Abderrahim; Saadoune, Ismael
Abstract : The lithiation of the SnP2 O7 anode material leads to tin extrusion and formation of Li x Sn alloys with stable capacity during the subsequent cycles. Abstract : SnP2 O7 was prepared by a sol–gel route. The structural changes of tin pyrophosphate during the electrochemical lithiation were followed by using in situ XRD measurements that reveal the existence of a crystalline phase at the beginning of the discharge process. Nevertheless, it becomes amorphous after the full discharge as a result of a conversion reaction leading to the formation of Li x Sn y alloys. The electrochemical tests show a high capacity with high retention upon cycling. To better understand the reaction mechanism of SnP2 O7 with Li, several techniques were applied, such as ex situ 119 Sn Mössbauer and ex situ 7 Li and 31 P NMR spectroscopies with which we can follow the changes in the local environment of each element during cycling.